2022
DOI: 10.3390/ijerph19052699
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Use and Efficacy of an Asynchronous Teledermatology System as a Novel Tool for Early Diagnosis of Skin Cancer during the First Wave of COVID-19 Pandemic

Abstract: Background: After the outbreak of the corona virus disease-19 (COVID-19) pandemic, teledermatology was implemented in the Hungarian public healthcare system for the first time. Our objective was to assess aggregated diagnostic agreements and to determine the effectiveness of an asynchronous teledermatology system for skin cancer screening. Methods: This retrospective single-center study included cases submitted for teledermatology consultation during the first wave of the COVID-19 pandemic. Follow-up of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
1
7
0
2
Order By: Relevance
“…Jobbágy et al showed that asynchronous teledermatology was an accurate skin cancer screening system during the first wave of the COVID-19 pandemic, examining 749 patients with 799 lesions using a mobile phone application. 84 Similar results were showed by Ziętek et al which analyzed 80 patients using remote dermatological consultation. 85 Finally, the long-term efficacy of telemedicine for patients with locally advanced basal cell carcinoma during COVID-19 pandemic has been reported by Villani et al 67 who analyzed 23 patients undergoing treatment with sonidegib, a hedgehog inhibitors, 86 performing monthly follow-ups by telemedicine.…”
Section: Teledermatology and Skin Cancerssupporting
confidence: 78%
“…Jobbágy et al showed that asynchronous teledermatology was an accurate skin cancer screening system during the first wave of the COVID-19 pandemic, examining 749 patients with 799 lesions using a mobile phone application. 84 Similar results were showed by Ziętek et al which analyzed 80 patients using remote dermatological consultation. 85 Finally, the long-term efficacy of telemedicine for patients with locally advanced basal cell carcinoma during COVID-19 pandemic has been reported by Villani et al 67 who analyzed 23 patients undergoing treatment with sonidegib, a hedgehog inhibitors, 86 performing monthly follow-ups by telemedicine.…”
Section: Teledermatology and Skin Cancerssupporting
confidence: 78%
“…The most important characteristics of a test for melanoma screening are the sensitivity and the negative predictive value [ 24 ], as false negative cases represent the most significant threat since the late diagnosis of melanoma increases mortality [ 2 , 3 ]. Dermoscopy is the most widely used non-invasive tool in the field of dermatology, with a sensitivity of 90% for melanoma diagnosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…57 While also emerging in other fields, telemedicine is very promising in dermatology, especially in regard to managing and triaging skin cancer patients. 58 Not only would automated mobile applications provide the physician with a first impression, but they could also serve as a filter by selecting more meaningful images for presentation. In addition, health care systems are typically at full capacity.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Telemedicine serves as an example of a possibility to help patients without risking the spread of infections as in the COVID‐19 pandemic 57 . While also emerging in other fields, telemedicine is very promising in dermatology, especially in regard to managing and triaging skin cancer patients 58 . Not only would automated mobile applications provide the physician with a first impression, but they could also serve as a filter by selecting more meaningful images for presentation.…”
Section: Opportunitiesmentioning
confidence: 99%